2019
DOI: 10.3389/fpsyg.2019.02489
|View full text |Cite
|
Sign up to set email alerts
|

Brief Sensory Training Narrows the Temporal Binding Window and Enhances Long-Term Multimodal Speech Perception

Abstract: Our ability to integrate multiple sensory-based representations of our surrounding supplies us with a more holistic view of our world. There are many complex algorithms our nervous system uses to construct a coherent perception. An indicator to solve this ‘binding problem’ are the temporal characteristics with the specificity that environmental information has different propagation speeds (e.g., sound and electromagnetic waves) and sensory processing time and thus the temporal relationship of a stimulus pair d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
(69 reference statements)
3
11
1
Order By: Relevance
“…The reduction in the TBW when training was performed with bright stimuli is consistent with previous reports ( De Niear et al., 2016 ; Powers et al., 2009 , 2012 ; Zerr et al., 2019 ). Our analysis also shows that this training effect is consistent with a shift in AV criterion placement, supporting evidence that trial-by-trial feedback can induce criterion shifts ( Aberg & Herzog, 2012 ) which can lead to performance improvements in perceptual tasks ( Herzog et al., 2006 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The reduction in the TBW when training was performed with bright stimuli is consistent with previous reports ( De Niear et al., 2016 ; Powers et al., 2009 , 2012 ; Zerr et al., 2019 ). Our analysis also shows that this training effect is consistent with a shift in AV criterion placement, supporting evidence that trial-by-trial feedback can induce criterion shifts ( Aberg & Herzog, 2012 ) which can lead to performance improvements in perceptual tasks ( Herzog et al., 2006 ).…”
Section: Discussionsupporting
confidence: 92%
“…Increases in TBW size have been associated with increased fall risk in older age ( Setti et al., 2011 ) and poorer performance on speech perception tasks ( Conrey & Pisoni, 2006 ; Stevenson et al., 2018 ). Training healthy individuals at an audiovisual SJ task led to lasting improvements in speech perception ( Zerr et al., 2019 ). Training with the specific aim to reduce the TBW has consequently been proposed as an intervention for those with multisensory deficiencies ( Foss-Feig et al., 2010 ; Powers et al., 2009 ; Setti et al., 2014 ; Stevenson et al., 2017 ; Wallace & Stevenson, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substantial evidence for altered audiovisual temporal binding in autistic youth, as well as observed relations between TBWs for audiovisual speech and other domains of functioning in autistic youth, has engendered increasing interest in the possibility of training audiovisual integration in autistic youth (e.g., Bahrick & Todd 2012 ; Cascio et al, 2016 ; Feldman et al, 2018 ; Zhou et al, 2020 ). A number of training studies targeting audiovisual temporal binding have been conducted in non-autistic adults, and have been shown to narrow TBWs in a relatively short period of time (i.e., 3–5 sessions; De Niear et al, 2016 , 2018 ; McGovern et al, 2016 ; Powers et al, 2009 ; Setti et al, 2014 ; Sürig et al, 2018 ; Zerr et al, 2019 ). These training paradigms provide automated feedback after each trial of a computerized task wherein participants must make judgements about the synchrony or temporal order of audiovisual stimuli, such as flashes and beeps (e.g., Powers et al, 2009 ; Setti et al, 2014 ; Sürig et al, 2018 ) and audiovisual speech, such as a speaker saying the syllable “ba” (De Niear et al, 2018 ).…”
Section: Perceptual Training Of Temporal Binding Of Audiovisual Stimulimentioning
confidence: 99%
“…There are several limitations to the literature on perceptual trainings for audiovisual stimuli in non-autistic adults. First, the majority of these perceptual training studies have found no evidence for generalization to untrained multisensory tasks (De Niear et al, 2018 ; Powers et al, 2016 ; Setti et al, 2014 ) or limited evidence for generalization (i.e., training effects only observed at limited SOAs or conditions in untrained tasks; Zerr et al, 2019 ). To date, only Sürig et al, ( 2018 ) have found strong evidence for generalization.…”
Section: Perceptual Training Of Temporal Binding Of Audiovisual Stimulimentioning
confidence: 99%